The use of governance instruments in health policies of developed countries (Economic and Political Thought, 2016)
This text is an analysis of selected aspects of public policies in the field ofhealth care in developed countries. They are tested for implementation of theGovernance concept. The aim of the study is to show the results of this analysisas a catalogue of good practices, which can provide recommendations forother countries, because implementation of governance is an opportunity tocreate effective policies in the social area.